2008
DOI: 10.1007/s12028-008-9145-0
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a New Coma Scale, the FOUR Score, in the Emergency Department

Abstract: The FOUR score can be reliably used in the ED by non-neurology staff. Both FOUR score and GCS performed equally well, but the neurologic detail incorporated in the FOUR score makes it more useful in management and triage of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
76
2
12

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 16 publications
5
76
2
12
Order By: Relevance
“…It does not include verbal response and therefore has a higher predictive value for patients in intensive care 14 . A recent study showed that the scale can be used successfully by different professionals from outside the field of neurosciences 22 . Although scales are of tremendous importance in assessing disorders of consciousness, it should be stressed that instruments intended to assess something as complex as consciousness naturally have certain limitations.…”
Section: Discussionmentioning
confidence: 99%
“…It does not include verbal response and therefore has a higher predictive value for patients in intensive care 14 . A recent study showed that the scale can be used successfully by different professionals from outside the field of neurosciences 22 . Although scales are of tremendous importance in assessing disorders of consciousness, it should be stressed that instruments intended to assess something as complex as consciousness naturally have certain limitations.…”
Section: Discussionmentioning
confidence: 99%
“…As a result probability of in hospital mortality is higher for the lowest total FOUR score when compared with that of GCS. FOUR score has been subjected to validation studies [11][12][13][14][15][16] in different scenarios like neuro ICU, emergency departments, medical ICU, comatose stroke patients in acute stroke unit , traumatic brain injuries etc. It has been compared with GCS in these validation studies and excellent inter rater agreements have been observed.…”
mentioning
confidence: 99%
“…A new coma scale, the Full Outline Of Unresponsiveness (FOUR) score, is gradually gaining acceptance because of an excellent inter-rater agreement, greater neurologic information, and a high predictive value [3,5,9,[12][13][14][15]. It quantifies consciousness by examining eye and motor responses, brainstem reflexes, and breathing pattern (each with a maximal value of 4).…”
mentioning
confidence: 99%
“…], and among examiners with different medical backgrounds and levels of experience [7][8][9][10][11][12][13][14][15]. In this issue, Marcati et al properly evaluate the Italian version of the FOUR score in 87 patients with acute brain injuries.…”
mentioning
confidence: 99%
See 1 more Smart Citation